Pengaruh E-Service Quality Dan E-Trust Terhadap E-Customer Loyalty Yang Dimediasi Oleh E-Satisfaction Pada Pengguna Aplikasi Alodokter Di Bandung Raya - Vinata, Putri Andin; Adialita, Tania (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The aim of this research is to examine the influence of e-service quality and e-trust on e-customer loyalty which is mediated by e-satisfaction of Alodokter application users in Greater Bandung. Respondents, including Generation Z and Millennials, had consulted using the Alodokter application. The objects assessed in this research were 120 respondents. The data collection technique used is convenience sampling which is included in non-probability sampling. In collecting data, researchers used a questionnaire distributed via Google Form. The data analysis technique used is descriptive analysis, simple and multiple linear regression using SPSS version 25 tools and using the Sobel test. The findings from this research are that e-service quality has a positive and significant effect on e-satisfaction, e-service quality and e-trust have a positive and significant effect on e-customer loyalty, and e-satisfaction plays a role in mediating the effect of e-service quality towards e-customer loyalty.